2020
DOI: 10.1093/jac/dkaa142
|View full text |Cite
|
Sign up to set email alerts
|

Levonadifloxacin, a recently approved benzoquinolizine fluoroquinolone, exhibits potent in vitro activity against contemporary Staphylococcus aureus isolates and Bengal Bay clone isolates collected from a large Indian tertiary care hospital

Abstract: Objectives Levonadifloxacin (WCK 771; IV) and its prodrug alalevonadifloxacin (WCK 2349; oral) are benzoquinolizine fluoroquinolones, recently approved in India for the treatment of acute bacterial skin and skin structure infections with concurrent bacteraemia and diabetic foot infections. Ahead of its market launch, the present study aimed to assess the in vitro activity of levonadifloxacin against contemporary Staphylococcus aureus isolates collected from a large tertiary care hospital in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…The observation in the present study is in agreement with these published findings. 7,[17][18][19][20][21] In this study, the clinical success rate of levonadifloxacin was >90% irrespective of IV or oral regimen, which was comparable to pivotal phase 3 trial in which levonadifloxacin IV and oral regimens demonstrated 91% and 95.2% clinical cure rates. Furthermore, no AEs were encountered for the evaluated 154 patients.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The observation in the present study is in agreement with these published findings. 7,[17][18][19][20][21] In this study, the clinical success rate of levonadifloxacin was >90% irrespective of IV or oral regimen, which was comparable to pivotal phase 3 trial in which levonadifloxacin IV and oral regimens demonstrated 91% and 95.2% clinical cure rates. Furthermore, no AEs were encountered for the evaluated 154 patients.…”
Section: Discussionsupporting
confidence: 74%
“…16 It should be noted that, levonadifloxacin is the lone available oral option with comprehensive coverage (>90% susceptibility) of gram-positive pathogens including MRSA; bestowed with safety features enabling longer duration of therapy. 21,22 With respect to comorbidities, apart from SIRS, patients under assessment were reported to have several complications which included sepsis. In such scenarios, a potent bactericidal antibiotic such as levonadifloxacin could be an ideal choice as compared to a slowly cidal or bacteriostatic antibiotic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Levonadifloxacin ((12 S )-7-fluoro-8-(4-hydroxypiperidin-1-yl)-12-methyl-4-oxo-1-azatricyclo[7.3.1.05,13]trideca-2,5,7,9(13)-tetraene-3-carboxylic acid) is the active S (−) isomer of nadifloxacin recently approved in India ( Figure 9 ) [ 194 , 195 ]. The S (−) isomer of nadifloxacin, has been shown to be more potent than the R (+) isomer and twice as active as the racemic form of nadifloxacin against Gram-positive and Gram-negative bacteria.…”
Section: Compounds In Therapy Since 2000mentioning
confidence: 99%
“…As a result, there is a significant increase in the potency of LND in acidic environments. [7][8][9] This feature could be beneficial for intracellular activity and antibacterial action in infections with an acidic environment.…”
Section: Levonadifloxacinmentioning
confidence: 99%
“…LND is S-(-)-9-fluoro-6,7-dihydro-8-(4-hydroxypiperidin-1yl)-5-methyl-1-oxo-1H,5H-benzo; quinolizine-2-carboxylic acid L-arginine salt tetrahydrate is the active S(-) isomer of nadifloxacin recently approved in India. [8] LND exhibits potent in vitro activity against contemporary S. aureus isolates and Bengal Bay Clone, isolates collected from a large Indian tertiary care hospital. [9] The S(-) isomer of nadifloxacin has been shown to be more potent than the R(+) isomer and twice as active as the racemic form of nadifloxacin against Gram-positive and Gram-negative bacteria.…”
Section: Levonadifloxacinmentioning
confidence: 99%